The 34th Annual Meeting of the Korean Society of Gynecologic Oncology 2019: meeting report - Yim, Ga Won (J Gynecol Oncol, 2019)
The 34th Annual Meeting of Korean Society of Gynecologic Oncology (KSGO) was held in Busan, Korea from 26 to 27 April. Around 460 Korean and international clinicians gathered in Busan to share and discuss their latest work and key issues of gynecologic oncologic research and treatment. The scope of this meeting included recent clinical trials and updates in gynecologic oncology, advances in ovarian cancer treatment, targeted therapy and immunotherapy in gynecologic cancer, management of hereditary gynecologic cancer, and newly revised staging of cervical cancer. As expected, the ongoing debate regarding the recent clinical trial on minimally invasive surgery for early-stage cervical cancer was addressed throughout the congress and the initial outline of the KSGO position statement was open for discussion. The meeting was an opportunity for all participants to come together and explore scientific insights of gynecologic cancer.